Dendritic cell immunoreceptor 2 (DCIR2) deficiency decreases hepatic conventional dendritic cell content but not the progression of diet‐induced obesity - Rossella Bellini; Annalisa Moregola; Jasmine Nour; Patrizia Uboldi; Fabrizia Bonacina; Giuseppe D. Norata (Immunity, Inflammation and Disease, 2023)
Abstract Aims Inflammatory pathways and immune system dysregulation participate in the onset and progression of cardiometabolic diseases. The dendritic cell immunoreceptor 2 (DCIR2) is a C‐type lectin receptor mainly expressed by conventional type 2 dendritic cells, involved in antigen recognition and in the modulation of T cell response. Here, we investigated the effect of DCIR2 deficiency during the development of obesity. Methods DCIR2 KO mice and the WT counterpart were fed with high‐fat diet (HFD) for 20 weeks. Weight gain, glucose and insulin tolerance were assessed, parallel to immune cell subset profiling and histological analysis. Results After HFD feeding, DCIR2 KO mice presented altered conventional dendritic cell distribution within the liver without affecting markers of hepatic inflammation. These observations were liver restricted, since immune profile of metabolic and lymphoid organs‐namely adipose tissue, spleen and mesenteric lymph nodes‐did not show differences between the two groups. This reflected in a similar metabolic profile of DCIR2 KO compared to WT mice, characterized by comparable body weight gain as well as adipose tissues, spleen, Peyer's patches and mesenteric lymph nodes weight at sacrifice. Also, insulin response was similar in both groups. Conclusion Our data show that DCIR2 has a redundant role in the progression of diet‐induced obesity and inflammation.